Application of Trichoderma sp. for enhancing growth and defence mechanism of red chilli (Capsicum annuum L.) cultivated under aluminum stress - Hazimah, Nabillah; Taufikurahman, Taufik; Iriawati (Institut Teknologi Bandung, 2025)
The extensive peatlands across Indonesia offer significant potential for cultivating food and horticultural crops, particularly red chili, a valuable commodity. However, these lands face significant challenges, including low pH levels and the presence of heavy metals, which can hinder plant growth. Heavy metals are harmful environmental pollutants that pose risks to agricultural land and plant health. Plant-microorganism interactions, like those with Trichoderma species, can boost plant growth and reduce aluminum (Al) toxicity. This study evaluated the effects of Trichoderma sp. on the growth and defense mechanisms of Tanjung variety chili plants under Al stress. The experiment used a Completely Randomized Design in factorial pattern with two factors: Trichoderma sp. at four levels (0 g, 10 g, 15 g, 30 g) and Al 0 ppm, 100 ppm, 200 ppm, 300 ppm). Observations included plant height, number of branches, plant dry weight, water content, total chlorophyll content, catalase and ascorbate peroxidase enzymes activity. The results indicated that 300 ppm Al reduced plant height to 14.22 ± cm, while adding 15 g Trichoderma sp. and 200 ppm Al increased plant height up to 20.2 ± 1.90 cm (control 15.14 ± 2.75 cm). 300 ppm Al reduced plant dry weight to 3.12 ± 0.12 g, but adding 15 g Trichoderma sp. increased plant dry weight to 8.29 ± 1.32 g compared to control (5.14 ± 0.46 g). The treatment of 30 g Trichoderma sp. without Al-induced increased total chlorophyll content (3.85 ± 0.9) (control 3.56 ± 0.90). Chili plants showed enhanced defence mechanism responses with higher CAT enzyme activity (27.95 ± 1.31 units/mg) when treated with 15 g of Trichoderma sp. and 300 ppm Al stress. Additionally, the application of 10 g of Trichoderma sp. under 300 ppm Al stress elevated APX enzyme activity to 0.111 ± 0.007 units/mg, and under 100 ppm Al stress. Thus, the treatment of 15 g and 30 g Trichoderma sp. effectively improved chilli plant growth and countered the adverse effects of Al stress.